A Rational Continuum: Legal and Cultural Abortion Narratives in Trump’s America - Eir-Anne Edgar (European Journal of American Studies)
Since Trump has taken office, the right to abortion is under threat. The composition of the Supreme Court can change quickly, giving the President opportunity to appoint justices he views as like-minded. This article examines Trump’s 2019 State of the Union address and the anti-abortion sentiments contained within in conjunction with the rights to personal privacy and reproductive choice established and maintained by US Supreme Court cases Roe v. Wade (1973), Planned Parenthood v. Casey (1992), and Whole Woman’s Health v. Hellerstedt (2016). This article posits that the legal status of abortion on a federal level is resolute, but socio-cultural narratives produced by the evangelical, conservative right threaten to undermine the legitimacy of those rights. Significantly, the attempted erasure of the right to privacy established in Roe signals a distressing trend, one that can be qualified as a general loss of self-determination over one’s body.